2008
DOI: 10.1016/j.cellbi.2008.09.004
|View full text |Cite
|
Sign up to set email alerts
|

A potential model for studying the plasticity and reprogramming of human epidermal stem cells through preimplantation blastocyst microinjection

Abstract: Microinjection of adult stem cells (ASCs) into blastocysts provides a classic model for studying ASC plasticity. To explore the molecular mechanisms that govern the reprogramming of ASCs, we evaluated the experimental model through microinjection of human epidermal stem cells (hEpiSCs) into mouse blastocysts. Mouse blastocysts underwent regular embryogenesis after microinjection of allogeneic cells, confirmed by morphological observation and embryo cell counting. hEpiSCs survive and integrate into mouse embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…As embryonic development progresses, these stem cells can redistribute and undergo further transdifferentiation under the influence of site-specific microenvironments. Thus, mice blastocyst injection and chimeras production is the best tool to determine the multi-directional differentiation potential of stem cells47. We found that hEMSCPCs injected into the mice blastocyst cavity formed heterogeneous chimeras.…”
Section: Discussionmentioning
confidence: 89%
“…As embryonic development progresses, these stem cells can redistribute and undergo further transdifferentiation under the influence of site-specific microenvironments. Thus, mice blastocyst injection and chimeras production is the best tool to determine the multi-directional differentiation potential of stem cells47. We found that hEMSCPCs injected into the mice blastocyst cavity formed heterogeneous chimeras.…”
Section: Discussionmentioning
confidence: 89%